Development of the controlling system in the management of dairy clusters - Vasylieva, Natalia; Васильєва, Наталя Костянтинівна; Velychko, Oleksandr; Величко, Олександр Петрович (Technology Center, 2017)
The issue of mathematical controlling in the dairy sector has been considered. The rank assessment to effectiveness of regional management in dairy clusters has been offered. The mathematical models of its improvement by means of the quickest spread of innovations, optimal reduction of expenditures, and grounded dependency between productivity and scale of production have been developed. The given complex of strategic and operative controlling has been verified in the article. Розглянуто проблему контролінгу в молочному секторі з засто-суванням математичних методів. Запропоновано рангову оцінку ефективності регіонального менеджменту молочних кластерів. Розроблено математичні моделі його вдосконалення шляхом найшвидшого поширення інновацій, оптимального скорочення витратної складової та обґрунтування залежності продуктивності від масштабів виробництва. У статті здійснено апробацію наведеного комплексу засобів стратегічного та оперативного контролінгу.
Розробка системи контролінгу в управлінні молочними кластерами
Keywords: strategic and operative controlling; cтратегічний та оперативний кон- тролінг; mathematical procedures of controlling; математичні процедури контролінгу; dairy cluster; молочний кластер; regional management; регіональне управління